PHONOLOGICAL VARIATION ON TOMUN LANGUAGES IN LAMANDAU, CENTRAL KALIMANTAN - Septiana, Dwiani; Yulianti, Andi Indah; Kurniati, Ai; Maharani, Amanda Vira (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
The Tomun language speakers are the community of Lamandau district and parts of the East Kotawaringin in Central Kalimantan. This study aims to determine the language’s status and document its phonological variations. The method used was qualitative, with linguistic data originating from language utterances spoken by the community in Lubuk Hiju, Guci, Delang, and Nanga Bulik Village, in Lamandau Regency, Central Kalimantan Province. Tomun language has seven vowel phonemes /a/, /i/, /u/, /e/, /ԑ/, /o/, and /ↄ/, three long vowels /i:/, /a:/, and /u:/, eighteen consonants: /b/, /c/, /d/, /g/, /j/, /k/, /p/, /t/, /ŋ/, /m/, /n/, /r/, /h/, /s/, /ɹ̱/, /w/, /y/, /l/, and double consonant: /bm/, /tn/, /kŋ/, /mp/. The Lubuk Hiju village shows a distinctive phonological variation solely used in that area. The phonemes are /ɛ/, /kŋ/, /bm/, /tn/, and /ɹ̱/. Based on dialectometric calculations, the Tomun language is part of Malayic Dayak with dialect variations, namely the Guci, Bulik, Delang, and Lubuk Hiju dialects.